2016
DOI: 10.3233/jad-150949
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 and Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is the most common form of dementia. Although the pathogenesis of AD remains unclear, AD is thought to result from an imbalance in the production and clearance of amyloid-β protein (Aβ). Aquaporin-4 (AQP4) is the major aquaporin in the mammalian brain, is mostly expressed on astrocytic endfeet, and functions as a water transporter. However, the distribution and expression of AQP4 are altered in both AD clinical populations and animal models. Recent studies have revealed that AQP4 is im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 70 publications
2
35
1
1
Order By: Relevance
“…Recent findings suggest that the brain lymphatic system contributes to clearing the majority of extracellular Aβ from the brain . The cerebral lymphatic system consists of two parts: glymphatic system in the brain parenchyma and lymphatic networks located in the dura mater .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings suggest that the brain lymphatic system contributes to clearing the majority of extracellular Aβ from the brain . The cerebral lymphatic system consists of two parts: glymphatic system in the brain parenchyma and lymphatic networks located in the dura mater .…”
Section: Introductionmentioning
confidence: 99%
“…These two systems seem to play a synergetic role in driving Aβ out of the brain, with each alteration potentially influencing the AD process . Suppression of glymphatic fluid transport has been observed in APP/PS1 transgenic AD model mice, with glymphatic malfunction seen prior to presence of substantial Aβ deposits .…”
Section: Introductionmentioning
confidence: 99%
“…36 Moreover, there have been interesting studies during recent years evaluating the distribution and expression of Aqp4 in preclinical and clinical AD studies. 37 In this context, experimental studies have already shown the role of Aqp4-dependent trans-astrocytic ISF bulk flow in the clearance of Aβ through the glymphatic system. 24,37,38 These results were confirmed with subsequent studies using Aqp4-knockout mice showing reduced A 40 clearance that resulted in Aβ deposition in the cortex and hippocampus.…”
Section: A Possible Role Of Transport Mechanisms?mentioning
confidence: 99%
“…37 In this context, experimental studies have already shown the role of Aqp4-dependent trans-astrocytic ISF bulk flow in the clearance of Aβ through the glymphatic system. 24,37,38 These results were confirmed with subsequent studies using Aqp4-knockout mice showing reduced A 40 clearance that resulted in Aβ deposition in the cortex and hippocampus. 32 Although there are no actual data indicating the modulatory role of sleep-wake cycles on the Aqp4 expression, awakened mice showed much-decreased clearance of exogenously applied Aβ from the interstitial space that was significantly reversed during sleep.…”
Section: A Possible Role Of Transport Mechanisms?mentioning
confidence: 99%
See 1 more Smart Citation